First tracks of newborn straight-tusked elephants (Palaeoloxodon antiquus) - Carlos Neto de Carvalho (Nature Portfolio, 2021)
Abstract Tracks and trackways of newborns, calves and juveniles attributed to straight-tusked elephants were found in the MIS 5 site (Upper Pleistocene) known as the Matalascañas Trampled Surface (MTS) at Huelva, SW Spain. Evidence of a snapshot of social behaviour, especially parental care, can be determined from the concentration of elephant tracks and trackways, and especially from apparently contemporaneous converging trackways, of small juvenile and larger, presumably young adult female tracks. The size frequency of the tracks enabled us to infer body mass and age distribution of the animals that crossed the MTS. Comparisons of the MTS demographic frequency with the morphology of the fore- and hind limbs of extant and fossil proboscideans shed light into the reproductive ecology of the straight-tusked elephant, Palaeloxodon antiquus. The interdune pond habitat appeared to have been an important water and food resource for matriarchal herds of straight-tusked elephants and likely functioned as a reproductive habitat, with only the rare presence of adult and older males in the MTS. The preservation of this track record in across a paleosol surface, although heavily trampled by different animals, including Neanderthals, over a short time frame, permitted an exceptional view into short-term intraspecific trophic interactions occurring in the Last Interglacial coastal habitat. Therefore, it is hypothesized that Neanderthals visited MTS for hunting or scavenging on weakened or dead elephants, and more likely calves.